Taxation : Finance Act 2005 - Melville, Alan. (Harlow, England ; New York : FT Prentice Hall/Financial Times, 2006)
This edition of the book gives a complete and up-to-date guide in accordance with the provisions of the finance act 2005. It describes the UK taxation system in sufficient clarity to meet the needs of those taking a study in taxation. The book has been made to explain the tax system as clearly as possible , with worked examples, review questions and solutions provided.
Includes index.
nmn, 11/08/16
Loan
Keywords: Taxation; Finance